E-POD investigations of turbulent premixed flame dynamics approaching lean blow-out conditions. Issue 1 (March 2023) - Meloni, Roberto; Chiarizia, Nicola; Nassini, Pier Carlo; Andreini, Antonio
Thanks to the continuous computational power increase, the use of high-fidelity computational fluid dynamics (CFD) simulations is nowadays customary, especially in the gas turbines design process. The extraordinary temporal and spatial detail of such analyses generate large datasets, which must be carefully studied to correlate different quantities and gain information to characterize the behavior of combustor designs. Several advanced post-processing tools have been proposed; however, the Extended-POD (E-POD) holds the greatest potential for turbulent combustion applications when the mutual influence of different quantities is the main goal of the investigation. The present work investigates the application of the E-POD to an LES model of a perfectly-premixed, swirl-stabilized, methane-air flame approaching Lean-Blow-Out. Leveraging the validation against the experimental data at two different operating conditions on a laboratory test case, the numerical model has been used to collect several quantities of interest for shedding light on the flow-flame interaction near the blow-out. The post-processing algorithm has been used to highlight the differences between two conditions approaching the extinction at distinct air-flow velocities. It has been found that, when the burner is operated with a higher velocity, the flame is subjected to a cyclic low-frequency breakdown around the internal recirculation zone, leading to an ingestion of cold products from the external parts of the combustor toward the center. Although other local effects acting on the flame brush have been found in both conditions, they are related mainly to higher order coherent structures with a lower energy content. As a result, their impact onto flame stability is found to be of secondary importance since their limited interaction with flame stabilization. The work shows that E-POD represents a powerful tool for investigating the key features of flame dynamics even at near-blow-out conditions, constituting a valid algorithm for interpreting the results of CFD analyses on gas turbines combustors.